Horsemanship for Women - Mead, Theodore H. (Theodore Hoe), 1837-; Parker, Gray (Salt Lake City, UT : Project Gutenberg, 2013)
"Horsemanship for Women" by Theodore H. Mead is a practical guide to horse training specifically tailored for women, written in the late 19th century. The book provides detailed lessons and techniques designed to help novice riders gain confidence and skill in managing and riding horses, emphasizing methods that avoid physical strength and focus instead on patience and understanding. The opening of the text introduces the reader to the author's experience in purchasing and training a horse named Sambo. The author engages in dialogue with his skeptical wife as he expresses his intent to train the horse despite her concerns about its suitability and his own inexperience. From the very first lesson, which involves getting the horse to come to him at the motion of a whip, the reader observes a progressive method that illustrates the value of gentle handling and kindness in gaining a horse's trust. The author recounts his initial challenges with Sambo, highlighting success through simple, clear communication and consistent practice, thus setting the stage for the systematic learning process that follows in the subsequent chapters. (This is an automatically generated summary.)
Release date is 2013-06-13
E-text prepared by Julia Miller, Paul Clark, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive/American Libraries (http://archive.org/details/americana)
Keywords: Horsemanship